The influence of digital marketing interaction on generation z consumer loyalty on local beauty products - Yasik, Yudi Limbar; Mutoffar, Muhamad Malik; Ridwan, Ridwan; Ginting, Jasa (Jurnal Mantik, 2025)
This study tried to look into how digital marketing interactions affect things on Generation Z consumer loyalty towards local beauty products in Indonesia. Regarding the digital transformation, Generation Z exhibits a strong tendency to engage actively in interactive communication with brands. This research adopted a quantitative explanatory approach using a survey methodology. Data were collected from 120 respondents aged 18–27 years who had used local beauty products within the last six months and were digitally active. The research instrument consisted of closed-ended questionnaires measured on a five-point Likert scale. Validity and reliability tests confirmed that the instrument met the required statistical standards. Tests of classical assumptions, encompassing normality, multicollinearity, and  hetero-scedasticity, also confirmed that the regression model was statistically valid. A simple linear regression analysis revealed that digital marketing interaction significantly and positively influenced consumer loyalty, The regression coefficient is 0. 532, and the significance level is 0. 000. The R Square value is 0. 521, which means that 52. 1% of the variation in consumer loyalty is explained by the model. The findings highlight the strategic importance of enhancing interactive digital marketing to foster emotional bonds and long-term loyalty among Generation Z consumers. This research adds value to existing knowledge by emphasizing interaction quality over mere digital presence